Examining correlates of alcohol related condom-less sex among youth living in the slums of Kampala, Uganda. Issue 10 (2nd October 2020) - Kumar, Sagar; Culbreth, Rachel E.; Swahn, Monica H.; Kasirye, Rogers
ABSTRACT: This study examined factors associated with alcohol related condom-less sex (ARCS) among youth living in Kampala, Uganda. Analyses are based on 2014 cross-sectional survey data of urban service-seeking youth participating in a Uganda Youth Development Link (UYDEL) drop-in center. The analytic sample consisted of only youth reporting alcohol use ( n = 347). Logistic regression analyses were computed to determine the factors associated with ARCS. In the bivariable analysis, ARCS was associated with being female (OR: 1.86; 95% CI: 1.21, 2.85), age of first drinking being between ages 13–16 (OR: 2.63; 95% CI: 1.42, 4.86), age of first time drunk being between ages 13–16 (OR: 2.88; 95% CI: 1.47, 5.67), binge drinking (OR: 3.64; 95% CI: 2.21, 5.98), rape (OR: 2.69; 95% CI: 1.64, 4.41), sex work (OR: 5.91; 95% CI: 3.09, 11.29), and being able to refuse sex when intoxicated (OR: 1.69; 95% CI: 1.10, 2.61). In the multivariable analysis, ARCS was associated with binge drinking (AOR: 2.97; 95% CI: 1.71, 5.17) and sex work (AOR: 3.48; 95% CI: 1.62, 7.49). These findings emphasize unmet needs of this population. Strategies seeking to prevent teenage alcohol use, particularly delaying initial alcohol use, may be beneficial for reducing ARCS in this population.